First Report on the Latvian SARS-CoV-2 Isolate Genetic Diversity - Zrelovs, Nikita; Ustinova, Monta; Silamikelis, Ivars; Birzniece, Liga; Megnis, Kaspars; Rovite, Vita; Freimane, Lauma; Silamikele, Laila; Ansone, Laura; Pjalkovskis, Janis; Fridmanis, Davids; Vilne, Baiba; et al. (Frontiers in Medicine, 2021)
Remaining a major healthcare concern with nearly 29 million confirmed cases worldwide at the time of writing, novel severe acute respiratory syndrome coronavirus - 2 (SARS-CoV-2) has caused more than 920 thousand deaths since its outbreak in China, December 2019. First case of a person testing positive for SARS-CoV-2 infection within the territory of the Republic of Latvia was registered on 2nd of March 2020, nine days prior to the pandemic declaration by WHO. Since then, more than 277 000 tests were carried out confirming a total of 1464 cases of COVID-19 in the country as of 12th of September 2020. Rapidly reacting to the spread of the infection, an ongoing sequencing campaign was started mid-March in collaboration with the local testing laboratories, with an ultimate goal in sequencing as much local viral isolates as possible, resulting in first full-length SARS-CoV-2 isolate genome sequences from the Baltics region being made publicly available in early April. With 133 viral isolates representing 9.1% of the total COVID-19 cases during the “first coronavirus wave” in the country (early March, 2020 – mid September, 2020) being completely sequenced as of today, here we provide a first report on the genetic diversity of Latvian SARS-CoV-2 isolates.